The Chemical components and antifungal and anti-mycotoxigenic (aflatoxin b1 and fumonisin b1) activity of star anise (Illicium verum) essential oils in Yen Bai Province, Vietnam - LOI, Nguyen Van; TUAN, Le Anh; BINH, Pham Thi; NGOC, Nguyen Thi Thanh (Food Science and Technology, 2023)
In Vietnam, star anise is grown in the provinces of Yen Bai, Ha Giang, Lao Cai, Lang Son, Bac Kan, and Cao Bang. The study aimed to analyze the chemical components, and antifungal and anti-mycotoxigenic (aflatoxin B1 and fumonisin B1) activity of star anise essential oils. By the gas chromatography mass spectrometry (GC-MS) method, 15 chemical components were predicted in the star anise essential oils. The major components were trans-anethole (67.05%), caryophyllene oxide (12.73%), limonene (4.27%), α-terpineol (2.43%), and myrcene (2.39%). The antifungal activity at 100 ppm recorded 85.24±0.05%, 76.73±0.06%, 69.37±0.02%, and 67.96±0.04% inhibition for Aspergillus flavus, Aspergillus parasiticus, Fusarium verticillioides, and Penicillium, respectively. Complete inhibition of 100% was observed at 200 ppm and 300 ppm for both A. flavus and A. parasiticus and at 400 ppm for F. verticillioides and Penicillium. Complete aflatoxin B1 inhibition was achieved at 100 and 200 ppm for A. flavus and A. parasiticus.